Do Calcifications on Mammography after Neoadjuvant Chemotherapy for Breast Cancer Always Need to be Excised? - Felicano, Yara (Ann Surg Oncol, 2017)
PURPOSE: To determine the relationship between mammographic calcifications and MRI tumoral enhancement before and after neoadjuvant chemotherapy (NAC) and assess the impact of these findings on surgical management. METHODS: This IRB-approved, HIPAA-compliant retrospective study involved breast cancer patients who underwent NAC between 2009 and 2015. 90 patients with pre- and post-treatment MRI and mammograms demonstrating calcifications within the tumor bed either at presentation and/or after treatment comprised the study cohort. Data gathered included pre- and post NAC imaging findings and post-NAC histopathology, particularly findings associated with calcifications. Comparisons were made using the Fishers Exact test with p-values < 0.05 considered significant. RESULTS: Complete resolution of MRI enhancement occurred in 44% and pathologic complete response (pCR) was achieved in 32% of patients. There was no statistically significant correlation between changes in calcifications and MRI (p=0.12). Resolution of enhancement was strongly correlated with pCR (p<.0001). The majority of patients with pCR demonstrated complete resolution of enhancement (23/29, 79%). No statistically significant relationship existed between changes in calcifications and rates of pCR (p=.06). PCR was most frequent in patients with resolution of enhancement and new, increasing, or unchanged calcifications (p<.0001). CONCLUSIONS: Although calcifications seen on post-NAC mammography may be associated with benign disease, loss of MRI enhancement does not predict the absence of residual tumor with sufficient accuracy to leave calcifications in place. Complete excision of tumor bed calcifications remains standard practice and a substantial limitation to NAC use for downstaging patients to be eligible for BCT.